The cancer glycocalyx mediates intravascular adhesion and extravasation during metastatic dissemination - Giovanni S. Offeddu; Cynthia Hajal; Colleen R. Foley; Zhengpeng Wan; Lina Ibrahim; Mark F. Coughlin; Roger D. Kamm (Communications Biology, 2021)
Offeddu et al. employ a microfluidic vascular model to study the effects of selective removal of glycocalyx components from cancer cells. They find that cancer-associated hyaluronic acid and CD44 mediate firm adhesion to endothelial cells and extravasation during metastasis.